Islamic Business Ethics in The Process of Termination of Employment Amid the Covid-19 Pandemic - Alam, Azhar; Isman, Isman; Indriyani, Latifah; Bafana, Faiz Adib (IJIBE (International Journal of Islamic Business Ethics), 2023)
This study aims to understand the application of Islamic business ethics in employee layoffs during the Covid-19 pandemic. This research method uses qualitative research methods. The data source is from the agenda of direct and indirect interviews with speakers selected by 10 participants: five entrepreneurs and five victims of layoffs. The finding shows that some business actors in Sukoharjo still need to understand the importance of instilling Islamic business ethics. This situation is proved by the discovery of ethical violations in doing business carried out by entrepreneurs, namely attaching importance to their business in the form of suddenly dismissing their employees, not giving severance pay to employees, being late in providing salaries, not being able to develop the business properly, and not instilling honesty. The violations committed by layoff victims are providing poor service, lack of expertise, and being undisciplined. This research should help future studies apply Islamic business ethics to layoffs. Islamic business principles protect entrepreneurs and layoff victims, allowing them to continue business during the pandemic and grow.